DEMOGRAPHIC CHANGES IN KHOREZM DURING THE SECOND WORLD WAR AND ITS CONSEQUENCES (TAMADDUN NURI JURNALI, 2024)
This article analyzes demographic changes in the Khorezm region during the Second World War. The article shows in percentage terms the contribution of men and women to mental and physical labor. Based on statistical documents, natural population growth and the number of births and deaths in the republic are revealed. It is shown that as a result of the relocation of the population to the region due to the war, various epidemic diseases arose, which led to illness and death of the local population.